Representing climate change in museum space and places. (8th November 2012) - Cameron, Fiona; Hodge, Bob; Salazar, Juan Francisco
Abstract: Museums and science centers hold a unique position in the media and political landscape as trusted information sources and are emerging as key players in climate change debates. The modes of engagement with audiences, visitors, and publics allow museums to provide sensorial and affective experiences though the agency of objects and immersive environments, which facilitate an active role on the part of audiences in cocreating narratives around climate change. This article draws on the research findings of an Australian Research Council Linkage project, Hot Science, Global Citizens: the agency of the museum sector in climate change interventions . Hot Science was an international, interdisciplinary project that interrogated the roles of museums and science centers in climate change as places to provide information, activate and broker discussions, and decisions around climate change issues, locally and transnationally. We put forward nine propositions, distilled from the project research findings and the sector‐wide views presented during a symposium held in 2011. We use these propositions to look critically at the ways in which climate change challenges the established concepts and practices of museums and science centers as places of influence, relevance, and certainty in an uncertain world. This includes, for example, the way science is produced, represented, and communicated. Recognizing the complexity and multiscalar nature of climate change entails building more effective responses that translate into action. The big task of the museum sector is not only to inform publics on the science of climate change but also to equip citizens with tactical knowledges that enable participation in actions and debates on climate change that affect their futures. WIREs Clim Change 2013, 4:9–21. doi: 10.1002/wcc.200 This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Communication Social Status of Climate Change Knowledge > Knowledge and Practice Trans‐Disciplinary Perspectives > Humanities and the Creative Arts